PENAFSIRAN HIND SHALABI MENGENAI KEDUDUKAN LAKI-LAKI DAN PEREMPUAN DALAM AL-QUR’AN - Fatihah, Fatihah; Abdul Aziz Shutadi, Abdul Aziz Shutadi; Agung NRS, Agung NRS; Ahmad Murtaza MZ, Ahmad Murtaza MZ (IJouGS: Indonesian Journal of Gender Studies, 2024)
The roles and positions of men and women have long been one of the most debated topics in society. This study examines Hind Shalabi's interpretation of the Qur'anic perspective on gender roles. Employing a qualitative methodology with library research as the primary data collection method, the study uses the Equilibrium Theory as an analytical framework. This theory emphasizes balance and mutual cooperation between men and women. The findings reveal that Hind Shalabi's interpretation of the Qur'an underscores the principle of equality between men and women, with her insights divided into several key themes. First, men and women are equal in dignity and standing (QS. Al-Hujurat [49]: 13). Second, both are obligated to maintain self-honor and chastity (QS. An-Nur [24]: 30–31). Third, men and women share equal accountability in fulfilling religious obligations (QS. Al-Ahzab [33]: 35). Fourth, they are encouraged to pursue knowledge together (QS. Al-Mujadila [58]: 11). Fifth, both are bound by the primordial covenant with Allah (QS. Al-Mumtahana [60]: 12). Sixth, men and women receive equal rewards for their faith and good deeds (QS. An-Nahl [16]: 97). Lastly, male and female thieves are subject to the same legal penalties (QS. Al-Maidah [5]: 38). By applying the Equilibrium Theory, Hind Shalabi asserts that men and women can effectively support and collaborate with one another in fulfilling their respective roles, fostering harmony and balance within society.